Variants and factors of catatonic syndrome pathomorphosis in the structure of endogenous catatonia - D. M. Safonov (Kazimierz Wielki University, 2018)
Urgency. Pathomorphosis of mental pathology leads to polymorphism or dissociation of its clinical manifestations, and, as a result, to difficulties in identification and differential diagnosis of individual psychopathological forms. Design. In order to establish the basic characteristics, variants and factors of the endogenic catatonia pathomorphism in schizophrenia patients, 144 individuals were examined. In the patients under examination the elements of endogenous catatonia were in the structure of various clinical forms of schizophrenia. Results. On the basis of a comparative analysis of the clinical and psychopathological characteristics of the catatonic syndrome in two ten - year periods pool of factors of endogenous catatonia pathomorphism, its structural and dynamic deviations were established. Conclusions. The main characteristics and tendencies of endogenous catatonia pathomorphism are determined. Four groups of catatonic syndrome pathomorphosis factors are identified and systematized: pharmacogenic, toxic, alternative, involutionary. Two vectors of pathomorphosis were systematized: functional (pharmacogenic and toxic groups) and morphological (alternative and involutionary groups).